Perbandingan Hasil Belajar Siswa Konsep Sistem Peredaran Darah Menggunakan Model Two Stay Two Stray (TSTS) dan Think Pair Share (TPS) di SMP Negeri 2 Seunagan Kabupaten Nagan Raya - Mauiza Hasanah (Biotik, 2015)
This study entitled: "Comparison of Student Learning Outcomes in Circulatory System Concepts with using Two Stay Two Stray (TSTS) and Think Pair Share (TPS) Models at SMP Negeri 2 Seunagan Nagan Raya". This study aims to figure out the differences in student learning outcomes in Circulatory System concept by using Two Stay Two Stray (TSTS) and Think Pair Share (TPS) models at SMP N 2 Seunagan Nagan Raya. The data were collected by using Library Research and Field Research. The population of this study were all students of VIII class in SMP Negeri 2 Seunagan Nagan Raya (60 people). The samples were 17 students of class VIII.2 and 17 students of class VIII.3. The technique used in collecting the data was learning outcomes test. The data were analyzed by using t test (t-count). The result showed that t-count was greater than t-table (t-count = 3.059>t- table = 2.037). it can be concluded that Two Stay Two Stray (TSTS) learning model is better than Think Pair Share (TPS) learning model in Circulatory Systems concept at SMP Negeri 2 Seunagan Nagan Raya, with the the average score in VIII.2 class (Two Stay Two Stray model) was 74.41 and the average score in VIII.3 class (Think Pair Share model) was 68.52.